Analysis of Service Quality on Community Satisfaction of Bogor Regency BAPPENDA Taxpayers - Banowati, Benna; Nurhayati, Popong; Asikin, Zenal (Dinasti Publisher, 2025)
This study aims to analyze the influence of service quality on taxpayer community satisfaction at the Regional Revenue Management Agency (BAPPENDA) of Bogor Regency. The research employed a quantitative approach using a survey method and Structural Equation Modeling Partial Least Squares (SEM-PLS) analysis. The measured dimensions of service quality include reliability, responsiveness, assurance, empathy, and tangibles, while community satisfaction serves as the dependent variable. The results indicate that the four dimensions of reliability, assurance, empathy, and tangibles have a positive and significant effect on community satisfaction. However, the responsiveness dimension does not show a significant influence. These findings suggest that information accuracy, staff professionalism, empathetic attitudes, and adequate service facilities are key factors in creating taxpayer satisfaction. On the other hand, response speed alone, without accurate resolution, is insufficient to improve public satisfaction. The implication of this study highlights the need to substantially enhance public service quality by strengthening reliability, transparency, and empathy to build a responsive and citizen-oriented tax administration system.